Suka Korea: Peniruan Perilaku Ala Korea di Kalangan Mahasiswa FISIP ULM - Titin Mardina; Varinia Pura Damaiyanti (Huma: Jurnal Sosiologi, 2023)
Korean popular culture or hallyu whose spread can influence students in accepting culture from outside. This study aims to find out the Korean cultural trends that students have followed and how the process of imitating the behavior of students who follow these trends. This study uses a qualitative research method with a phenomenological approach. Data collection techniques used are observation, interviews and documentation. The results of this study indicate that FISIP ULM students have known Korean popular culture trends since they were in elementary school until now through watching Korean dramas on television and getting to know Korean music/K-pop through YouTube. From Korean dramas and K-pop, students learn about other trends, such as Korean fashion, Korean specialties and the Korean language. Trends in Korean popular culture that have been followed by FISIP ULM students are Korean drama shows, Korean music/K-pop, Korean-style fashion, Korean specialties and Korean language. Then, from getting to know the trend of Korean popular culture, students are interested in imitating the behavior of actors and actresses in Korean dramas and also their K-pop idols. Trends that are imitated such as clothing styles that give a casual but relaxed look, more colorful and simple, minimalist make-up displays, and hairstyles that they like as well as trends in Korean food and Korean language that make them curious and interested in trying and learning it.